Policy of Local Head of Post Election (Study at The Office of Cooperatives and SMEs Regional Tomohon) - Willians Gratiano Timpal; Evi Elvira Masengi; Selpius R. Kandou; Tartius Timpal (Journal of Social Science, 2022)
This study aims to describe the Post Regional Head Policy (Study at the Tomohon Regional Cooperative and SMEs Service). This study uses qualitative research methods and uses data collection techniques: Interview, Observation and Documentation. The primary data sources in this study were the results of direct interviews and observations conducted by researchers on state civil apparatus at Tomohon Cooperative and SMEs Regional Office, and secondary data sources were official government documents, books, journal articles and internal organization records in this case the Cooperatives and Cooperatives Office. Tomohon Regional SMEs. The results of the study indicate that: The policy of the regional head greatly affects the running of the government, in this case the Tomohon Regional Cooperative and SMEs Office. What happened at the Cooperatives and SMEs Regional Office of Tomohon was that the assignment of state civil apparatus positions was not in accordance with applicable regulations or rules based on elements of subjectivity and politics. What should be done based on the State civil apparatus performance assessment by prioritizing the achievement system and career system, in practice it is contrary to what is expected. The element of subjectivity and politics has a very high role in making regional head policies to determine the position of state civil apparatus in this service, in this case related to the granting of structural positions or dismissal from structural positions or even job transfers.